Archaeocercus gen. nov. (Hymenoptera, Chalcidoidea, Encyrtidae) from Late Eocene Rovno Amber - Simutnik, S. A.; Perkovsky, E. E. (Zootaxa, 2018)
Archaeocercus schuvachinae, gen. et sp. nov., is described and illustrated based on a female specimen from Rovno amber (Ukraine). This fossil genus is characterized by the apical position of cerci on metasoma, absence of filum spinosum on distal margin of linea calva on forewings, triangular hypopygium reaching metasomal apex, mesoscutum with incomplete notauli, long veins on forewings and apically expanded antennae. A brief comparative morphological analysis of some structures of the extinct and extant Encyrtidae is provided. The new genus is considered unplaced within Encyrtidae.